2016
DOI: 10.1016/j.nlm.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in plasticity, synaptic, glia and connectivity protein levels in rat dorsal hippocampus

Abstract: Thus far the identification and functional characterization of the molecular mechanisms underlying synaptic plasticity, learning, and memory have not been particularly dissociated from the contribution of developmental changes. Brain plasticity mechanisms have been largely identified and studied using in vitro systems mainly derived from early developmental ages, yet they are considered to be general plasticity mechanisms underlying functions -such as long-term memory- that occurs in the adult brain. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 111 publications
(150 reference statements)
7
61
2
Order By: Relevance
“…Recently, we showed that IA experiences in infant rats, although apparently forgotten, are actually stored over the long‐term in a latent form, as these memories can be reinstated later in life if reminders are experienced (Travaglia, Bisaz, Sweet, Blitzer, & Alberini, ). Contrary to what had been suggested previously, we found that the infant hippocampus (at postnatal day 17, PN17) is highly responsive and engaged in learning, and makes a necessary contribution to the formation of the latent, long‐lasting memories by recruiting molecular mechanisms typical of critical periods (Travaglia, Bisaz, Cruz, & Alberini, ; Travaglia et al, ). Hence, we suggested that, as in other brain functions and systems, the episodic learning system undergoes a critical period, during which the hippocampal system acquires functional competence through experience (Alberini & Travaglia, ).…”
Section: Role Of Astrocyte–neuron Metabolic Coupling In Memory Formatcontrasting
confidence: 99%
“…Recently, we showed that IA experiences in infant rats, although apparently forgotten, are actually stored over the long‐term in a latent form, as these memories can be reinstated later in life if reminders are experienced (Travaglia, Bisaz, Sweet, Blitzer, & Alberini, ). Contrary to what had been suggested previously, we found that the infant hippocampus (at postnatal day 17, PN17) is highly responsive and engaged in learning, and makes a necessary contribution to the formation of the latent, long‐lasting memories by recruiting molecular mechanisms typical of critical periods (Travaglia, Bisaz, Cruz, & Alberini, ; Travaglia et al, ). Hence, we suggested that, as in other brain functions and systems, the episodic learning system undergoes a critical period, during which the hippocampal system acquires functional competence through experience (Alberini & Travaglia, ).…”
Section: Role Of Astrocyte–neuron Metabolic Coupling In Memory Formatcontrasting
confidence: 99%
“…Interestingly, examination of control groups indicated that for both placebo pellet controls and untreated controls there was a significantly higher rate of neurogenesis for males than females. Although not significant for the other control groups, this post-SHRP increased rate of neurogenesis for males is consistent with a growth spurt period in hippocampus (Bayer, 1980; Bayer & Altman, 1974; Travaglia et al, 2016) and makes the decrease in neurogenesis for corticosterone-pellet-males even more significant. It is possible that the increased rate of neurogenesis during this developmental window produces a vulnerability to glucocorticoid perturbation specifically in males, though given the relatively high level of neurogenesis in males receiving a placebo pellet and the small sample size of untreated controls, these results must be considered preliminary until replicated.…”
Section: 0 Corticosterone Effects On Neurogenesissupporting
confidence: 60%
“…Developmentally, the ability to acquire trace eyeblink conditioning emerges postnatally and becomes robust by about 28 days of age in the rat, corresponding to the prolonged maturation of hippocampal and cortical circuits during the first several weeks (Ivkovich et al, 2000b; Travaglia et al, 2016). If corticosterone’s effects are mediated by hippocampus, we should see deficits similar to those reported by Ivkovich and Stanton (2001) where hippocampal lesions on postnatal day 10 impaired subsequent trace eyeblink conditioning on Days 25–26 but not delay eyeblink conditioning at matching inter-stimulus intervals.…”
Section: 0 Introductionmentioning
confidence: 99%
“…Meanwhile, striking differences between early stage and adult molecular and functional organization of the hippocampus question the relevance of these molecular mechanisms, as these adult plasticity markers are poorly expressed during early-life (Travaglia et al 2016). These concerns are supported by numerous in vitro findings showing opposing, stimulatory effects of pro-inflammatory cytokines on plasticity molecules, such as CaMKII, tyrosine kinases, mitogen-activated protein kinases (MAPKs), protein kinase C (PKC), phosphoinositide-3 kinase (PI3K) and transcription factors such as nuclear factor kappa B (NF-κB) and activator protein 1 (AP-1) (Rosenberg 2002; Wu et al 2004, 2009).…”
Section: Introductionmentioning
confidence: 99%